18F-fluorodeoxyglucose positron emission tomography in malignant pleural mesothelioma: diagnostic and prognostic performance and its correlation to pathological results. (31st January 2020) - Lococo, Filippo; Rena, Ottavio; Torricelli, Federica; Filice, Angelina; Rapicetta, Cristian; Boldorini, Renzo; Paci, Massimiliano; Versari, Annibale
Abstract: Although 18 F-fluorodeoxyglucose positron emission tomography/computed tomography (PET/CT) scan has been generally validated in the staging of malignant pleural mesothelioma (MPM), its diagnostic and prognostic performances are not clearly established. Aiming to identify possible factors causing 18 F-fluorodeoxyglucose PET/CT false-negative results and influencing prognosis in MPM patients, we analysed clinical, radiometabolic and pathological features in 141 MPM patients who underwent diagnostic 18 F-fluorodeoxyglucose PET/CT scan (January 2009–July 2018) at 2 high-volume institutions. The Fisher's exact test and the Cox model were used in statistical analysis. Overall detection rate was 88.3% with 16 patients (11.6%) presenting with a standardized uptake value (SUV) max <2.5 (PET-negative). PET-negative cases were more frequently detected in older patients ( P = 0.027) and early-stage tumours (33.3% false-negative in stage I and 40.0% false-negative in T1-tumours, with P = 0.014 both). Mean SUVmax value was higher in sarcomatoid (11.8 ± 4.6) and biphasic MPM (9.3 ± 7.0), rather than in epithelioid MPM (6.9 ± 3.8, P < 0.001). Concerning overall survival, SUVmax (both as continuous and as categorical variable) was found to be a prognostic factor, in addition to stage ( P = 0.032) and histology ( P = 0.014) as confirmed by multivariable analysis (hazard ratio 2.65, confidence interval 1.23–5.70; P < 0.001). In the light of such results, we highlight that a low fluorodeoxyglucose uptake might be observed in more than 10% MPMs, especially in early-stage tumours affecting elderly patients. Furthermore, high SUVmax values significantly correlated with a worse prognosis.